THE POLITICAL PARTICIPATION OF THE PEOPLE IN THE LOCAL GOVERNMENT THEPSATHIT DISTRICT, CHAIYAPHUM PROVINCE - Jayamedhi (Klinsrisuk), Phramaha Thatsapong; Promgun, Suraphon; Huatsri, Chanchai (Journal of Graduate MCU KhonKaen Campus, 2021)
The objectives of this research were: 1) to study the level of political participation of the people in local government in Thep Sathit District, Chaiyaphum Province; 2) to study the level of political participation of the people in local administration in Thep Sathit District 3) to compare the political participation of the people in local administration in Thep Sathit District, classified by the samples’ personal factors and by political participation according to the Aparihāniya-Dhammas; 4) to promote the political participation of the people in local government in Thep Sathit District. The samples of this study included 397 participants and the tools used were: questionnaires and interviews. The data were analyzed to find the following statistical values: Frequency, Percentage, Mean, Standard Deviation; while for hypothesis testing, t-test and F-test. The data were analyzed by descriptive interpretation. The research results were as follows: 1) The political participation of the people in the local government in Thep Sathit District in overall was at a moderate level. 2) The political participation according to the Aparihāniya-Dhammas in overall was at a moderate level. 3) The results of comparing the political participation of the people in local government in Thep Sathit District: people with different sexes get involved in politics in local government in overall indifferently. For the people with different age, education, occupation, income, and the Aparihāniya-Dhammas, their participation in politics in overall was different. 4) Suggestions are that in people should participate in inspecting the local government in order to make transparent. The people should participate in the development of their local policies. The people have to think together to raise suggesting the problem condition and government to summarize the issues in order of importance. local government should be thoroughly monitored through online media channels and publicity boards. Keywords : Participation; politics; Local government